2021
DOI: 10.1136/bmjopen-2020-048331
|View full text |Cite
|
Sign up to set email alerts
|

Using the Functional Resonance Analysis Method to explore how elastic compression therapy is organised and could be improved from a multistakeholder perspective

Abstract: ObjectivesElastic compression stocking (ECS) therapy is an important treatment for patients with deep venous thrombosis (DVT) and chronic venous insufficiency (CVI). This study aimed to provide insight into the structure and variability of the ECS therapy process, its effects on outcomes, and to elicit improvement themes from a multiple stakeholder perspective.DesignThirty semi-structured interviews with professionals and patients were performed. The essential functions for the process of ECS therapy were extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(30 citation statements)
references
References 46 publications
0
30
0
Order By: Relevance
“…Anonymity between participants is guaranteed, which prevents bias resulting from opinions from dominant participants influencing group opinion ( 20 , 21 ). We modified the procedure for the qualitative first round as used in the classic Delphi analysis and instead used the content derived from two of our earlier performed studies in this context (a Functional Resonance Analysis method and a Realist evaluation) to develop the questionnaire ( 16 , 17 ). CREDES criteria were used to conduct and report the study ( 22 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Anonymity between participants is guaranteed, which prevents bias resulting from opinions from dominant participants influencing group opinion ( 20 , 21 ). We modified the procedure for the qualitative first round as used in the classic Delphi analysis and instead used the content derived from two of our earlier performed studies in this context (a Functional Resonance Analysis method and a Realist evaluation) to develop the questionnaire ( 16 , 17 ). CREDES criteria were used to conduct and report the study ( 22 ).…”
Section: Methodsmentioning
confidence: 99%
“…We invited a panel of 56 Dutch health care professionals with a balanced representation of all professional groups involved in ECS therapy (i.e., internists, dermatologists, general practitioners, emergency room nurses, home care nurses, medical stocking suppliers, and occupational therapists) and seven patients ( 16 ). The participants included local stakeholders as well as national stakeholders to assure broad support of the consensus reached.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The organization of compression therapy is complex and involves collaboration between the patient and various healthcare professionals. There is considerable variation in how compression therapy is organized for both DVT and CVD patients [ 10 ]. In this study, this variability was found to affect patient’s chances to remain self-reliant, the advised treatment duration for DVT patients, and was expected to affect compliance with compression therapy.…”
Section: Introductionmentioning
confidence: 99%